A Short-Acting GLP-1 Analog or Prandial Insulin to Supplement Basal Insulin?—Moving Toward Personalized Management of Type 2 Diabetes Mellitus. Issue 3 (May 2014) - Hirsch, Irl B.; Schneider, Doron; King, Aaron; Polonsky, William H.; Reid, Timothy S.; Shubrook, Jay; Verderese, Carol A.; Wallace, Jeffrey; Riddle, Matthew C.
Abstract : : New models of health care delivery that emphasize patient-centered care affirm the need for alternatives to add-on prandial insulin therapy when optimized basal insulin fails to maintain glycemic control in patients with type 2 diabetes mellitus. Regimens that are easy to teach, convenient, and flexible generally improve the outlook for long-term success. Our review reconsiders traditional barriers to insulin intensification in primary care and provides an illustration of how the benefits and drawbacks of > 1 choice of action—specifically, adding rapid-acting insulin or a short-acting glucagon-like peptide-1 analog—can be weighed by the patient and provider together to determine the best next treatment step that balances efficacy, safety, and adherence to therapy. Technological, organizational, and interpersonal strategies for applying personalized management at this often challenging crossroads of diabetes management are also described.